Unraveling the Mechanism of Purple Leaf Formation in Brassica napus by Integrated Metabolome and Transcriptome Analyses - Li, Haibo; Du, Yi; Zhang, Jinkun; Feng, Huimin; Liu, Jianguo; Yang, Guiling; Zhu, Yunna (Frontiers in Plant Science, 2022)
Brassica napus as both oilseed and vegetable, is widely cultivated in China. The purple leaf of B. napus is rich in anthocyanins and can provide valuable nutrients. Although several high-anthocyanin cultivars have been reported, the molecular mechanism underlying anthocyanin biosynthesis in B. napus remains lesser-known. Therefore, in this study, we conducted integrative metabolome and transcriptome analyses in three B. napus cultivars with different leaf colors. Overall, 39 flavonoids were identified (including 35 anthocyanins), and 22 anthocyanins were differentially accumulated in the leaves, contributing to the different leaf colors. Cyanidin-3,5,3'-O-triglucoside was confirmed as the main contributor of the purple leaf phenotype. Meanwhile, other anthocyanins may play important roles in deepening the color of B. napus leaves. A total of 5069 differentially expressed genes (DEGs) and 32 overlapping DEGs were identified by RNA-sequencing; hence, the correlation between anthocyanin content and DEG expression levels was explored. Two structural genes (DFR and ANS), three GSTs (homologous to TT19), and 68 differentially expressed transcription factors (e.g., MYB, bHLH, WRKY, and ERF) were identified and found to contribute to anthocyanin accumulation, biosynthesis, or transport in B. napus leaves. The findings of this study provide new insights into the regulatory network underlying anthocyanin accumulation in B. napus.